Traditional beliefs a boon or a curse in rearing a newborn - M., Prasanna; M., Pranam G.; Hirevenkanagoudar, Usha; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2025)
Background: Traditional beliefs in rearing newborns are deeply rooted in the history and culture of a community. They reflect the values, norms, and experiences of a society and often vary significantly from one culture to another. These practices can be influenced by factors such as geography, religion. Methods: A cross-sectional study was conducted at Navodaya medical college and research centre, Raichur and Selected UHTC and PHC’S of Raichur from July 1, 2024 to July 31 2024. A total of 100 mothers and grandparents were interviewed and data was collected after taking consent. Results: In our study 6% of mothers discarded colostrum. Around 8% of mothers gave pre-lacteal feeds. Around 26% of mothers poured oil into ears, 91% of mothers applied oil on head. Conclusions: The study reveals that while mothers value traditional beliefs in newborn care, integrating these practices with modern medical advice is crucial for promoting infant health and ensuring culturally sensitive healthcare.